THE EFFECT OF MARKETING PROMOTION MANAGEMENT ON PUBLIC SERVICE ADVERTISING IN STRENGTHENING DIGITAL COMMUNICATION - Syahrial Shaddiq; M. Iwu Iyansyah; Shintia Sari; H.M. Zainul (SMBJ: Strategic Management Business Journal, 2021)
The dynamics of digital communication literacy today cannot be separated from technological advances, also every person or institution/government or other private institution is always faced with the development of human resources. Moreover, related to the planned production, this shows the ability to process marketing propositions and advertisements, both commercial advertisements and public service advertisements (PSA) in the midst of strengthening communication literacy itself. This research was conducted using descriptive qualitative research methodology, namely digging up data by direct observation, and interviews with those who can be used as data sources. The purpose of this research is to provide a clear description of the Effect of Marketing Promotion on Public Service Advertising on Strengthening Digital Communication Literacy, as well as to contribute ideas to policy makers and other researchers in the future, thereby providing significant benefits to these problems.